Crystallisation temperature control of stoichiometry and selectivity in host–guest compounds. Issue 39 (25th September 2017) - Sykes, Nicole M.; Su, Hong; Weber, Edwin; Bourne, Susan A.; Nassimbeni, Luigi R.
Abstract : A bulky diol host is only selective for tertiary butanol when versus 2-propanol at low temperatures. Abstract : The host H, 9, 9′-(ethyne-1, 2-diyl)bis(fluoren-9-ol), has been employed to study its selectivity towards the close boiling alcohol pair, 2-propanol and tertiary butanol. H is selective for tertiary butanol at low temperatures, but includes both guests without discrimination at high temperatures. Concomitantly higher guest/host ratios were observed at lower temperatures, in agreement with the literature. The kinetics of solid–host: guest–vapour enclathration was successfully measured by powder X-ray diffraction.